Merjenje tlakov plevralnega prostora med razbremenilno punkcijo (plevralna manometrija) kot varna in objektivna metoda pri ocenjevanju vpliva plevralnega izliva na izražanje simptomov - Meglič, Anita (Zdravniški vestnik, 2022)
Background: Patients with pleural effusion often require therapeutic thoracentesis (TT), which results in more or less pronounced dyspnea relief. Due to safety concerns, it is recommended to remove up to a maximum of 1500 mL effusion in one session. Methods: 96 patients in whom TT was indicated were included in the study. VAS dyspnea score before, immediately after, two hours after TT, and in 73 patients additionally 24 hours after TT was collected. The amount of fluid removed was measured. During TT, water manometer was used to measure pleural pressures, from which pleural space elastance was calculated. Based on their elastance curves characteristics, the patients were divided into different groups. Results: We found a correlation between initial pleural pressure/volume of effusion removed and dyspnea relief after TT. TT was most often terminated due to the onset of symptoms, in 16 patients it was terminated due to pleural pressure measurement. 74 patients were classified in the group with a normal elastane curve, in 22 patients we detected unexpandable lungs. Although more than 1500 mL of effusion was removed in 32 (33%) patients, there were no important complications during TT. Conclusion: Higher initial pleural pressure is weakly correlated with higher initial dyspnea and greater dyspnea relief after TT. The dynamic of pleural pressure change is useful for detecting unexpandable lungs during TT. During TT with pleural manometry, more than 1500 mL of pleural fluid can be safely removed.
Keywords: Dispneja; Dyspnea; Lung; plevralna punkcija; plevralni izliv; Pljuča; Visual analogue scale; Vizualna analogna lestvica